BASIC ACTIVITIES FOR TEACHING THE PRAGMATICS OF COMPLAINING TO L2 LEARNERS - Hasanova Umida Odiljon qizi (Лучшие интеллектуальные исследования, 2023)
Annotation: In this article, basic activities of teaching pragmatics of complaining and its steps and strategies as well are given in order to make L2 learners be aware of using the language appropriately. It is also provided with examples and some exercises which can be useful in teaching pragmatics of complaint.